Postmortem findings in non-human primates from Pernambuco, Brazil (Research, Society and Development, 2022)
This study analyzed necropsy reports and photographic records of non-human primates from the Pathology Division of the Department of Veterinary Medicine at the Federal Rural University of Pernambuco (UFRPE), Brazil. Pathological data of 60 non-human primates (NHP) necropsied between January 2017 and December 2018 were analyzed based on the following criteria: city and zone (urban, peri-urban, and rural), origin (free-living and captivity), history and suspected clinical diagnosis, sex, species, age, corpse’s conservation status, and macroscopic anatomopathological findings. The anatomopathological findings of viable necropsied animals (53.33%) were statistically analyzed for absolute and relative values. The primary causes of death were trauma injury (42%), parasitism (5%), pneumonia (3%), and fetal dystocia (3%).  Trauma, possibly caused by anthropization, was the most prevalent cause of the primates' death. This conclusion presents an important differential diagnosis in primate death evolution during the epizootic period.